O intérprete educacional de língua brasileira de sinais (IELIBRAS) atuante na UFS : em cena a construção de sua identidade profissional - Santos Filho, Genivaldo Oliveira (2018)
The role of the Libras Educational Interpreter is of great importance because it gives the deaf student access to knowledge. It is necessary, however, to prepare this professional so that his identity is recognized. This research aims to understand and analyze, based on narratives, how the professional identity of the Libras Educational Interpreter has been constructed in the context of the Federal University of Sergipe. In the empirical scenario of the research, the presence of this professional was highlighted as of 2011, in particular, under Law 12,319 / 2010. Under these circumstances, it is asked: how the Libras Educational Interpreter has been building his professional identity at the Federal University of Sergipe? The methodological path, of qualitative exploratory character, gained direction through narratives of the subjects chosen for this purpose - Libras Educational Interpreters. As a theoretical contribution, researchers and scholars were consulted, such as Perlin (2006), Gesser (2006), Schein (1996) on identity; Constâncio (2010), Martins (2009), Gurgel (2010) for the Interpreter in higher education. Questionnaires were also used composed of open and closed questions with the purpose of tracing the profile of professional interpreters. The analysis of the data was obtained taking as a starting point the Critical Narrative Analysis (ACN), from Mota (2013), with an acute reading of the text on a phenomenological look and circular hermeneutical technique of pre-comprehension and understanding of the phenomenon studied. And so, the narrative is divided into three expressive discursive instances, namely: it begins with the language resource (Content plane), running through the meaning effect (Language plan) and arrives at the moral of the story.( world model plan). The results were obtained from the following episodes: Formation of being an interpreter; Function of the interpreter; Identification with work; Professional dilemmas; Pathways to valorization. These episodes demonstrate that, in the narratives, many factors contribute to the construction of the professional identity, since, for the narrators of the research, the presence of the educational interpreter causes that the deaf university students have, besides the access to the knowledge, the opportunity education and, in fact, the expansion of the educational space. And so, the interpreters conclude that they intermediation between all the involved ones - teachers, students and servers -, and in the way, also, contribute to the constitution of Education Inclusive University.